2019
DOI: 10.1519/jsc.0000000000003123
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transcranial Direct Current Stimulation With Caffeine Intake on Muscular Strength and Perceived Exertion

Abstract: Lattari, E, Vieira, LAF, Oliveira, BRR, Unal, G, Bikson, M, de Mello Pedreiro, RC, Marques Neto, SR, Machado, S, and Maranhão-Neto, GA. Effects of transcranial direct current stimulation with caffeine intake on muscular strength and perceived exertion. J Strength Cond Res 33(5): 1237–1243, 2019—The aim of this study was to investigate the acute effects of transcranial direct current stimulation (tDCS) associated with caffeine intake on muscular strength and ratings of perceived exertion (RPE). Fifteen healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 33 publications
0
30
0
1
Order By: Relevance
“…Over 20 new studies explored the effects of caffeine on different muscular endurance outcomes [6,8,9,11,16,21,22,26,29,30,35,36,38,41,44,45,48,49,[52][53][54][55]]. An ergogenic effect of caffeine on muscular endurance was observed in the majority of these studies, with the effect sizes ranging from small to large (Cohen's d: 0.18-2.21).…”
Section: Muscular Endurancementioning
confidence: 99%
“…Over 20 new studies explored the effects of caffeine on different muscular endurance outcomes [6,8,9,11,16,21,22,26,29,30,35,36,38,41,44,45,48,49,[52][53][54][55]]. An ergogenic effect of caffeine on muscular endurance was observed in the majority of these studies, with the effect sizes ranging from small to large (Cohen's d: 0.18-2.21).…”
Section: Muscular Endurancementioning
confidence: 99%
“…Eleven reviews were identified and excluded, and 90 studies were screened for titles and abstracts. Then, 77 studies were excluded, and 13 were screened for full-texts, resulting in 6 studies for inclusion (3,35,43,46,47,59). The authors included 7 studies manually (13,26,42,58,73), 6 were found in the reference list of the studies, and 2 (19,44) were suggested to be included by the author (E.L.), considering that these studies were not found in the search or the references' lists.…”
Section: Resultsmentioning
confidence: 99%
“…Transcranial direct current stimulation consists of a noninvasive neuromodulatory technique that depolarizes (anodal stimulus) or hyperpolarizes (cathodal stimulus) the neuronal membrane (23). Also, when anodal tDCS (a-tDCS) is applied over the left DLPFC, there is evidence of an increased number of repetitions and a reduction in rating of perceived exertion (RPE) in both upper- (18) and lower-body (17) exercises, when compared with a sham stimulus (i.e., inactive form of stimulation used to control for the placebo effect). Given the relationship between the PFC and pleasure responses (27), there is indirect evidence suggesting that the improvements in volume obtained through the use of a-tDCS could be associated with psychological changes (i.e., perceived exertion and pleasure) (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Also, when anodal tDCS (a-tDCS) is applied over the left DLPFC, there is evidence of an increased number of repetitions and a reduction in rating of perceived exertion (RPE) in both upper- (18) and lower-body (17) exercises, when compared with a sham stimulus (i.e., inactive form of stimulation used to control for the placebo effect). Given the relationship between the PFC and pleasure responses (27), there is indirect evidence suggesting that the improvements in volume obtained through the use of a-tDCS could be associated with psychological changes (i.e., perceived exertion and pleasure) (17,18). However, this effect of a-tDCS applied over the left DLPFC on pleasure has not been assessed in RT yet, especially when a lower-body exercise is performed following an upper-body exercise.…”
Section: Introductionmentioning
confidence: 99%